The primary somatosensory sensory cortex-basolateral amygdala pathway contributes to comorbid depression in spared nerve injury-induced neuropathic pain - Guo Chen; Min Luo; Wentao Chen; Yu Zhang; Zuchao Gu; Miaomiao Xu; Ying Zhang; Jiang Bian (Scientific Reports)
Abstract Comorbid depression in chronic pain is a prevalent health problem, yet the underlying neural mechanisms remain largely unexplored. This study identified a dedicated neural circuit connecting the hind limb region of the primary somatosensory cortex (S1HL) to the basolateral amygdala (BLA) that mediated neuropathic pain-induced depression. We demonstrated that depressive-like behaviors in the chronic phase of a mouse neuropathic pain model were associated with heightened activity in the S1HL and BLA. Using viral tracing and RNAscope in situ hybridization, we characterized the circuit architecture of S1HL glutamatergic projections to BLA cholecystokinin (CCK) neurons (S1HLGlu → BLACCK). In vivo fiber photometry calcium imaging revealed that both the S1HL BLA-projecting afferents and the BLA S1HL-innervating neurons exhibited hyperactivity in neuropathic pain-induced depressive states. Chemogenetic inhibition of the S1HL → BLA circuit could block neuropathic pain-induced depressive-like behaviors. In addition, specific knockdown of CCK expression in BLA S1HL-innervating neurons alleviated these depressive-like behaviors. Our findings demonstrated that the cortical-amygdala circuit S1HLGlu → BLACCK drove the transition from chronic pain to depression, thus suggesting a potential neural circuit basis for treating chronic pain-related depressive disorders.